Application of multi-component reaction for covalent immobilization of two lipases on aldehyde-functionalized magnetic nanoparticles; production of biodiesel from waste cooking oil. (March 2020) - Ashjari, Maryam; Garmroodi, Maryam; Amiri Asl, Fatemeh; Emampour, Mahsa; Yousefi, Maryam; Pourmohammadi Lish, Mitra; Habibi, Zohreh; Mohammadi, Mehdi
Graphical abstract: Highlights: Two lipases were covalently immobilized on aldehyde-functionalized nanoparticles. Leaching experiment confirmed covalent nature of the linkage. The thermal and co-solvent stability of the immobilized derivatives were greatly improved. All the derivatives were used to catalyze biodiesel production from waste cooking oil. The effect of different parameters on biodiesel yield was studied by Response Surface Methodology Abstract: Lipase from Rhizomucor miehei (RML) and Thermomyces lanuginosa lipase (TLL) were immobilized on silica core-shell magnetic nanoparticles (Fe3 O4 @SiO2 ) produced by coating Fe3 O4 core with silica shell. The nanoparticles were functionalized with aldehyde groups followed by immobilization of RML and TLL by using a multi-component reaction in an extremely mild condition. Rapid immobilization of both enzymes (1.5−12 h) with high immobilization yields (81–100%) was observed. The maximum loading capacity of the support was determined to be 81 mg for RML and 97 mg for TLL. The thermal stability of the immobilized derivatives of RML and TLL were greatly improved by retaining 54 and 97 % of their initial activities at 65 °C, respectively. The immobilized preparations were used to produce biodiesel by transesterification of waste cooking oil. In an optimization study, Response Surface Methodology (RSM) and a central composite rotatable design (CCRD) were used to study the effect of amount of biocatalyst, temperature, reaction time, water adsorbent (wt.%) and ratio of t -butanol to oil (wt.%) on the yield of biodiesel production. Biodiesel production yield by immobilized TLL reached 93.1 % under optimal conditions while the maximum yield for RML was 57.5 %. Both immobilized derivatives showed high reusability after 5 cycles of the reaction.